Rock Physical Model and AVO Patterns for the Mud-Rich Source Rock - Yu, Songhe; Zong, Zhaoyun; Yin, Xingyao (Frontiers in Earth Science, 2021)
Rock physical model and amplitude variation with offset (AVO) patterns considering the content of organic matter and the composition of minerals have a wider significance for guiding the identification and prediction of the mud-rich source rock. A rock physical model is proposed for describing the elastic properties of kerogen in different maturity stages. The proposed rock physical model builds an intrinsic connection between the elastic properties and physical parameters of the mud-rich source rock, thereby providing a theoretical basis for a seismic inversion and a seismic forward modeling. To overcome the limitations of laboratory measurement, a combination-four-parameter regression (CFPR) method is further proposed to estimate the continuous total organic carbon (TOC) values for the verification and analysis of the rock physical model. The modeling results reveal that the P-wave velocity and P-wave impedance will decrease with an increase in TOC, and the Poisson ratio and Poisson impedance will increase as the mud content increases, which are consistent with the conclusions of the cross plot using the actual well data. Based on the proposed rock physical model, the seismic responses of the mud-rich source rock are further modeled. The synthetic seismic records are consistent with the well-side seismic records, the top reflection of the mud-rich source rock behaves as a stronger negative event dimming with an incident angle corresponding to a class IV AVO pattern, and the bottom reflection exhibits a class I AVO anomaly. In addition, a two-layer model is constructed to analyze an effect of the TOC content and mud content on the AVO characteristics. The results indicate that increasing the TOC content and mud content will significantly increase the interceptions and slightly change the gradients of the P-P reflection coefficients. These results help to guide the identification and evaluation of the mud-rich source rock.